2021
DOI: 10.1177/0956462421990281
|View full text |Cite
|
Sign up to set email alerts
|

BASHH 2018 UK national audit of HIV partner notification

Abstract: HIV partner notification (PN) is a highly effective strategy to identify people living with undiagnosed HIV infection. This national audit of HIV PN is against the 2015 British Association of Sexual Health and HIV (BASHH)/British HIV Association (BHIVA)/Society of Sexual Health Advisers (SHAA)/National AIDS Trust (NAT) HIV PN standards, developed in response to the 2013 BASHH/BHIVA national HIV PN audit. We report significant improvements in the number of contacts tested per index case, likely due, in part, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…15,33 We found that programs in which HIV positivity among tested partners is high can still have low case-finding and that HIV positivity in tested partners explains a minority of the variance in case-finding between programs. These observations support the use of the indices used to monitor syphilis APS for decades in the United States and the United Kingdom 18,27 and should prompt Presidents Emergency Plan for AIDS Relief, CDC, and ministries of health around the world to adopt a more comprehensive approach to APS program assessment that includes traditional APS STD indices-not just HIV positivity in tested partners -in program monitoring and evaluation.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…15,33 We found that programs in which HIV positivity among tested partners is high can still have low case-finding and that HIV positivity in tested partners explains a minority of the variance in case-finding between programs. These observations support the use of the indices used to monitor syphilis APS for decades in the United States and the United Kingdom 18,27 and should prompt Presidents Emergency Plan for AIDS Relief, CDC, and ministries of health around the world to adopt a more comprehensive approach to APS program assessment that includes traditional APS STD indices-not just HIV positivity in tested partners -in program monitoring and evaluation.…”
Section: Discussionmentioning
confidence: 64%
“…The erosion of APS effectiveness in high-income nations does not seem to be confined to the United States and stands in contrast to most recent findings from lowincome and middle-income nations. A 2016 national audit of APS conducted in the United Kingdom reported an interview case-finding index=0.065, 27 only slightly higher than that seen in the United States and substantially lower than the index of 0.12 reported from a similar UK audit performed in 2011. 28 By contrast, recent program evaluations conducted in low-income and middle-income countries have reported interview case-finding indices from 0.12 to 0.45, 5,[29][30][31][32] highlighting that the value of APS varies dramatically based on epidemiologic context.…”
Section: Discussionmentioning
confidence: 72%
“…The program’s productivity was particularly strong among recently diagnosed ICs (case finding index = 0.29) compared with ICs who had been enrolled in care for more than 6 months (case finding index = 0.07). Ukraine’s overall HIV case finding index was comparable of superior to rates observed in the US in 2019 (0.054) [ 17 ], the UK in 2018 (0.066) [ 16 ], Botswana in 2018–2020 (0.14) [ 12 ], and Namibia in 2019–2021 (0.14) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, multiple studies have evaluated IT in the USA, Western Europe and sub-Saharan Africa, but few studies have done so in Eastern Europe 3 5 9–14. Ukraine has the second largest population of PLHIV, approximately 240 000 people, in Eastern Europe and Central Asia, a region leading the world in HIV epidemic growth in recent years 15–17.…”
Section: Introductionmentioning
confidence: 99%
“…Recent observational studies of scaled IT programmes describe variable success in HIV case-finding across low-income, middle-income and high-income settings 9 10 13 14. Reported case finding indices, representing the number of newly diagnosed partners identified per participating IC, have varied from 5.4 newly diagnosed partners per hundred participating ICs (0.054) in the USA in 2019 to 14 newly diagnosed partners per hundred participating ICs (0.14) in Botswana in 2018–2020 9 14.…”
Section: Introductionmentioning
confidence: 99%